The acute effects of combined static and dynamic stretch protocols on fitness performances in soccer players - Amiri-Khorasani, M.; Sotoodeh, V. (The Journal of Sports Medicine and Physical Fitness, 2013)
Aim: The purpose of this study was to compare the acute effects of different stretching methods on acceleration, speed, agility, power, and flexibility in different soccer positions. Methods and results: Therefore, 16 soccer players conducted 10 m, 20 m, shuttle run agility, vertical jump, and V-sit flexibility after static (SS), dynamic (DS), combined (static + dynamic) (CS), and no stretching (NS). Relative to the no-stretching condition, there were significant differences in fitness performances after (1) DS vs. SS, (2) DS vs. CS, and (3) CS vs. SS in defenders, midfielders, strikers, and also in all players (PConclusion: In conclusion, it may be desirable for soccer players to perform DS during warm up prior to the performance of activities that require a high power output.